THE EFFECT OF THE DIFFERENTIATED LEARNING-BASED PROJECT BASED LEARNING MODEL ON THE LEARNING OUTCOMES OF SPEECH TEXT WRITING SKILLS OF GRADE VII STUDENTS OF SMP NEGERI 5 TOBADAK - Murni R, Dewi; Haslinda, Haslinda; Rosmini, Rosmini (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to test the effect of the application of the Project Based Learning (PBL) learning model based on differentiated learning on the speech text writing skills of grade VII students at SMP Negeri 5 Tobadak. This study used an experimental design with a pretest and posttest to measure the improvement of speech writing skills before and after the application of the learning model. The study sample consisted of 22 students who were randomly selected simply, divided into an experimental group and a control group. The results showed that the experimental group that received the differentiated learning-based PBL model treatment experienced a significant improvement in speech text writing skills, with the average posttest score increasing from 59.5 on the pretest to 85.3, or an increase of 25.8 points. Meanwhile, the control group that followed conventional learning only increased by 12.6 points (from 60.5 to 73.1). These results show that the application of the PBL learning model based on differentiated learning is more effective in improving speech text writing skills compared to conventional learning. This learning model is able to accommodate different learning styles, interests, and readiness of students, so that they can improve their comprehension, creativity, and writing skills more optimally. These findings provide empirical evidence that contextual and differentiational learning strategies are effective in improving learning outcomes, especially in speech writing skills at the junior high school level.